Hubungan Kepemimpinan yang Melayani dan Kepemimpinan Karismatik Terhadap Efikasi Diri - Muhammad Yid’ril Suwidi; Anwar Mansyur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the relationship between serving leadership variables, charismatic leadership on self-efficacy. this study uses a method with a quantitative approach using sampling techniques, the sample used is 106 respondents. this research data collection technique uses a questionnaire, the test stage in this study is instrument test, model test and hypothesis testing using spss (25). the test results of the data show that the serving leadership variable with the results has a positive and insignificant effect on self-efficacy then for the charismatic leadership variable with the results has a significant positive effect on self-efficacy. Keywords: servant leadership; charismatic leadership; self-efficacy